Etoposide and cisplatin in combination with anlotinib for lung NUT carcinoma: a case report - Sun, Yuxing; Bian, Jiangyu; Wang, Linfeng; Zhang, Tong (Frontiers in Oncology, 2025)
Lung NUT carcinoma is a rare malignant tumor, which is highly aggressive, poorly differentiated, and difficult to recognize at an early stage, and is associated with very rare reports and extremely poor prognosis, with some reports showing a mOS of only 2.2 months. In this paper, we report the treatment of a rare case of primary lung NUT cancer. After surgery, chemotherapy and targeted therapy, the patient’s progression-free survival is now more than 4 months, which provides a feasible treatment option for lung NUT cancer.